Juridical review of decision number 547/pid.b/2020/pn. Jap on murder with the element of intentionality - Rizki, Rizki; Silitonga, Luhut Immanuel; Sirait, Dedy Gokvala (Journal of Law Science, 2024)
Today's technological developments encourage humans to follow thought patterns and lifestyles to keep up with the times. Murder is one of the impacts of this development, in the Criminal Code murder is classified as a crime against life whose regulation is specifically regulated in Chapter XIX which consists of 13 articles. One of the cases is Decision Number 547/Pid.B/2020/PN. Jap where the perpetrator committed murder intentionally. The problem formulation of this research is how the legal regulation of the criminal act of murder with an element of intent is in positive law in Indonesia and how the judge considers it in decision no. 547/Pid.B/2020/PN. Japan. About murder with an element of intent. The research method used in this research is normative juridical, data collection techniques are carried out using literature, the type of data used is secondary data, and the data analysis used in this research is descriptive qualitative. In Indonesian positive law, there are various considerations that are taken into account in assessing the crime of murder, such as the condition of the perpetrator, motive and condition of the victim.